Avoiding Cascading Protection Tripping in Transmission Systems and Assessment of Quality and Security of Protection System - Krebs, Rainer; Ziegler, Gerhard; Jäger, Johann; Balasiu, Florin; Lazar, Felicia (IEEE PES PowerTech2009, 2009)
This paper describes typical developments of blackouts from simple cause to cascading outages. The involvement of the protection system at the beginning and during the enlargement of the incident to the blackout will be shown. Measures to avoid cascading protection tripping will be presented. A new method will be proposed to assess the quality and security of protection systems which can be applied online and offline for systems with up to some ten thousand relay